Literature Review: Peran Ibu dalam Keberhasilan Pemberian ASI Eksklusif - Yenny Rahmawati; Hapsari Windayanti; Indriyani Suroso; Kurniawati; Amilatun Azizah; Sairoh; Tri Fitriana Sakti (Prosiding Seminar Nasional dan CFP Kebidanan Universitas Ngudi Waluyo, 2024)
The World Health Organization Who (2019) recommends to mothers around the world to breastfeed their babies exclusively for the first 6 (six) months after the baby is born to achieve optimal growth, development and health. This recommendation has been followed by various countries in the world, one of which is Indonesia. UNICEF (United Nations International Children's Emergency Fund) states that 30 thousand deaths of children under five in Indonesia and 10 million deaths of children under five worldwide every year can be prevented through exclusive breastfeeding for 6 months from the first after the birth of the baby without giving additional food and drinks to the baby. The Indonesian government realizes the importance of infants' right to exclusive breastfeeding and its impact by issuing a series of restrictions. The provisions of Government Regulation No. 33 of 2012 clearly stipulate that "every mother who gives birth must give exclusive breast milk to the baby born except in the event that there is a medical indication, the mother is not present and the mother is separated from the baby or in other words it can be said that it is a necessity for the mother who gives birth to refuse the feeding of infant formula milk and other baby products. Although breastfeeding has become an Indonesian culture, efforts to improve the behavior of exclusively breastfeeding mothers are still needed because in reality the practice of exclusive breastfeeding has not been fully implemented. One of the reasons for the unsuccessful implementation of exclusive breastfeeding in Indonesia is the factor of working mothers. The purpose of this literature review is to find out the relationship between mothers' work and the success of exclusive breastfeeding. A total of 4 articles obtained from the google schooler and pubmed databases that match keywords with the inclusion criteria for articles published in 2019-2024, can be accessed in full pdf and are review articles. The results of the literature review of the 4 articles showed that there was a significant relationship between mothers' work and exclusive breastfeeding Conclusion, Mother's work is an important factor for the success of exclusive breastfeeding. Abstrak World Health Organization Who (2019) merekomendasikan kepada ibu di seluruh dunia untuk menyusui bayinya secara ekslusif selama 6 (enam) bulan pertama setelah bayi dilahirkan untuk mencapai pertumbuhan, perkembangan dan kesehatan yang optimal. Anjuran tersebut telah diikuti oleh berbagai negara di dunia, salah satunya Indonesia. UNICEF (united nations international children’s emergency fund) menyatakan bahwa 30 ribu kematian anak balita di indonesia dan 10 juta kematian balita diseluruh dunia setiap tahun dapat dicegah melalui pemberian ASI Ekslusif selama 6 bulan sejak pertama setelah kelahiran bayi tanpa memberikan makanan dan minuman tambahan kepada bayi. Pemerintah indonesia menyadari pentingnya hak bayi atas ASI ekslusif dan dampaknya dengan mengeluarkan serangkaian perindang-undangan. Ketentuan PP No. 33 tahun 2012 jelas mengatur bahwa  setiap ibu yang melahirkan harus memberikan ASI Eksklusif kepada bayi yang dilahirkan kecuali dalam hal terdapat indikasi medis, ibu tidak ada dan ibu terpisah dati bayinya atau dengan kata lain bisa dikatakan keharusan bagi ibu yang melahirkan untuk menolak pemberian susu formula bayi dan produk bayi lainnya. Meskipun menyusui bayi sudah menjadi budaya Indonesia, namun upaya meningkatkan perilaku ibu menyusui ASI eksklusif masih diperlukan karena pada kenyataannya praktek pemberian ASI Eksklisif belum dilaksanakan sepenuhnya. Salah satu penyebab belum berhasilnya pelaksanaan ASI eksklusif di Indonesia adalah faktor ibu yang bekerja. Tujuan dari literatur review ini adalah untuk mengetahui hubungn pekerjaan Ibu terhadap keberhasilan pemberian ASI eksklusif. Sebanyak 4 artikel yang didapat dari data base google schooler dan pubmed yang sesuai kata kunci dengan kriteria inklusi artikel terbit tahun 2019-2024, bisa diakses full pdf dan merupakan artikel ulasan review. Hasil literature review dari 4 artikel tersebut, menunjukkan bahwa ada hubungan yang signifikan antara pekerjaan ibu dengan pemberian ASI ekslusif Kesimpulan, Pekerjaan ibu merupakan faktor yang penting bagi keberhasilan pemberian ASI eksklusif.